Fasudil Is an Effective Graft Vasodilator for Gastroepiploic Artery in Coronary Artery Bypass Grafting. Issue 4 (July 2015) - Watanabe, Go; Yamaguchi, Shojiro; Tomita, Shigeyuki; Nishida, Yuji
Abstract : Objective: The gastroepiploic artery (GEA) has been used as an alternative arterial in situ graft for coronary artery bypass grafting (CABG). However, because of the large individual differences and the spastic nature of the GEA, caution has to be exercised during harvesting. We evaluated the usefulness of fasudil, a Rho kinase inhibitor, as a vasodilator for right GEA (RGEA) graft after harvesting, compared with the conventional agents papaverine and verapamil-nitroglycerin. Methods: Between June 2009 and January 2013, 30 patients with ischemic heart disease who underwent isolated CABG using RGEA graft were randomly assigned to fasudil (n = 10), papaverine (n = 10), or verapamil-nitroglycerin (n = 10) group. Fasudil (2.67 mmol/L), papaverine (1.0 mmol/L) mixed with heparinized blood, or verapamil-nitroglycerin (30 μmol/L each) was injected intraluminally into the RGEA graft after harvesting. Right GEA graft free flow (GFF), hemodynamic changes, and histopathology of RGEA were evaluated. Results: Intraluminal injection of fasudil increased GFF significantly ( P < 0.001) and markedly from 41.5 ± 31.5 mL/min at baseline to 149.3 ± 46.7 mL/min after injection. Papaverine increased GFF ( P < 0.001) from 40.0 ± 35.8 to 64.9 ± 33.7 mL/min, and verapamil-nitroglycerin also increased GFF ( P < 0.001) from 38.8 ± 32.1 to 79.0 ± 35.2 mL/min. The GFF was significantly higher ( P = 0.001) in the fasudil group than in the other two groups. Histopathologically, fasudil treatment markedly increased the diameter of RGEA graft, while maintaining integrity of the multiple elastic lamellae. Blood pressure did not change significantly after drug injection in all groups. Conclusions: Fasudil is more potent than papaverine or verapamil-nitroglycerin in increasing GFF of RGEA graft for CABG.